2017
DOI: 10.1128/mcb.00165-17
|View full text |Cite
|
Sign up to set email alerts
|

RNA Binding by Histone Methyltransferases Set1 and Set2

Abstract: Histone methylation at H3K4 and H3K36 is commonly associated with genes actively transcribed by RNA polymerase II (RNAPII) and is catalyzed by Saccharomyces cerevisiae Set1 and Set2, respectively. Here we report that both methyltransferases can be UV cross-linked to RNA in vivo. High-throughput sequencing of the bound RNAs revealed strong Set1 enrichment near the transcription start site, whereas Set2 was distributed along pre-mRNAs. A subset of transcripts showed notably high enrichment for Set1 or Set2 bindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 68 publications
2
33
0
Order By: Relevance
“…Activation of Rad6/Bre1 and COMPASS recruitment also require interactions with the Ser-5 phosphorylated CTD of RNA polymerase II, providing a tight transcriptional connection ( Krogan et al, 2003 ; Ng et al, 2003 ; Xiao et al, 2005 ). COMPASS recruitment then occurs through interactions of Swd2 with active H2B-associated Rad6/Bre1, and of Set1/Spp1 with nascent mRNA ( Battaglia et al, 2017 ; Luciano et al, 2017 ; Sayou et al, 2017 ; Thornton et al, 2014 ). In mammals, additional CxxC domains in Cfp1 (the orthologue of yeast Spp1) and some SET-domain proteins further specify and diversify COMPASS activity, allowing DNA methylation-dependent activity and selective recruitment of COMPASS to promoter and enhancer sequences ( Brown et al, 2017 ; Clouaire et al, 2012 ; Hu et al, 2017 ; Thomson et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Activation of Rad6/Bre1 and COMPASS recruitment also require interactions with the Ser-5 phosphorylated CTD of RNA polymerase II, providing a tight transcriptional connection ( Krogan et al, 2003 ; Ng et al, 2003 ; Xiao et al, 2005 ). COMPASS recruitment then occurs through interactions of Swd2 with active H2B-associated Rad6/Bre1, and of Set1/Spp1 with nascent mRNA ( Battaglia et al, 2017 ; Luciano et al, 2017 ; Sayou et al, 2017 ; Thornton et al, 2014 ). In mammals, additional CxxC domains in Cfp1 (the orthologue of yeast Spp1) and some SET-domain proteins further specify and diversify COMPASS activity, allowing DNA methylation-dependent activity and selective recruitment of COMPASS to promoter and enhancer sequences ( Brown et al, 2017 ; Clouaire et al, 2012 ; Hu et al, 2017 ; Thomson et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Activation of Rad6/Bre1 and COMPASS recruitment also require interactions with the Ser-5 phosphorylated CTD of RNA polymerase II, providing a tight transcriptional connection (Krogan et al, 2003;Ng et al, 2003;Xiao et al, 2005). COMPASS recruitment occurs through interactions of Swd2 with active H2B-associated Rad6/Bre1, and of Set1/Spp1 with nascent mRNA (Battaglia et al, 2017;Luciano et al, 2017;Sayou et al, 2017;Thornton et al, 2014). In mammals, additional CxxC domains in Cfp1 (the orthologue of yeast Spp1) and some SETdomain proteins further specify and diversify COMPASS activity, allowing DNA methylationdependent activity and selective recruitment of COMPASS to promoter and enhancer sequences (Brown et al, 2017;Clouaire et al, 2012;Hu et al, 2017;Thomson et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…As a positive control, CRAC data for the RNA-binding protein Nab3 ( Bresson et al, 2017 ) were similarly analyzed and identified the previously reported UUCU-binding site. Analysis of negative control data from the BY control strain, Rpo21 (the large subunit of RNAPII) or the histone methyl-transferases Set1 and Set2 ( Sayou et al, 2017 ), identified no clearly enriched motifs.…”
Section: Resultsmentioning
confidence: 99%
“…PCR duplicates that were not collapsed during preprocessing due to sequencing errors or differential trimming at the 3’ end were collapsed ( Tuck and Tollervey, 2013 ). After the exclusion of reads mapping to RNAPI and RNAPIII transcripts or originating from the mitochondrial genome ( Sayou et al, 2017 ), reads mapping to protein-coding genes and containing single nucleotide deletions (indicating the precise nucleotide crosslinked to the bait protein) were selected using pyReadCounters from pyCRAC ( Webb et al, 2014 ). To remove biases in sequence representation caused by abundantly expressed genes, overlapping reads were assembled into a single sequence using pyClusterReads from pyCRAC ( Webb et al, 2014 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation